Elecciones en Latinoamérica. 1985-2015, 30 años de transformación democrática. Leandro Querido y Fernando Domínguez Sardou (comps.), Buenos Aires, Editorial Dunken, 2017, 334 págs. - Marco, María Victoria (2017)
Fil: Marco, María Victoria. Pontificia Universidad Católica Argentina; Argentina